Resistensi Perempuan Seni Kontemporer: Membangun Subjektivitas Melalui Perilaku Komunikasi Komunitas Perempuan Xpresif - Ratna Damayati; Farida Nurul Rahmawati (Jurnal Riset Komunikasi (JURKOM), 2025)
Power relations based on patriarchal hierarchies strengthen the marginalization of contemporary women artists in Bangkalan Regency, in the form of social pressure, negative stigma, and dominant norms. The Xpresif Women's Community was formed as an effort to seize control over life narratives and build a more complete identity. This study aims to reveal the communication behavior and forms of resistance of contemporary art women in the Perempuan Xpresif community. Using qualitative methods with data collection through observation, interviews and documentation. Referring to James C. Scott's theory of resistance and Hélène Cixous' theory of feminist body writing, the results show that the resistance carried out is divided into two forms, namely open resistance and closed resistance. Open resistance is in the form of rejecting the rules of power relations, indifference by surviving to become a woman of art and giving birth to performance art works such as Matodus which challenges stereotypes of women's bodies. Closed resistance is carried out such as hiding art activities, hidden cries, and symbolic actions as a strategy to maintain autonomy over their bodies.